Trihalomethanes Formation Potential in Water Supply System of Bandar Abbas (Southern Iran): from Source to Distribution Network - Leila rezaei; Vali Alipour; Sakine shokooheyan; Amin Ghanbarnejad (Shiraz University of Medical Sciences, 2014)
Background: Pre-chlorination of raw water containing natural organic matters may lead to forming harmful disinfection by-products such as trihalomethanes (THMs), the measurement of which needs expensive advanced analytical instruments. This study was conducted to anticipate THMs formation potential in Bandar Abbas drinking water system using cheap and simple experiments and a mathematical model. Methods: In a 24 week sampling program, 96 samples were collected weekly from raw water (RW), clarification (CE), filtration (FE), and disinfection effluent (DE). After measuring the Dissolved Organic Carbon (DOC), residual chlorine, contact time, temperature and pH of water, THMs concentration was calculated using a mathematical model. Results: The means of DOC concentration in RW, CE, FE and DE were 5.56, 4.21, 3.50, and 3.01 (mg/l), respectively. The mean of temperature values varied from 22.28 in RW to 21.25 in DE and the mean of pH variations was measured from 6.75 in DE to 8.37 in CE. Also, the mean of residual chlorine concentration was 0.0 to 1.72 in RW and DE, respectively. Conclusion: The means of calculated THMs were 37.92±4.82μg/l, 51.15±9.44μg/l, and 52.71±8.37μg/l for CE, FE, and DE respectively; this did not meet the related EPA standard (30- 40μg/l); therefore, further detailed studies should be conducted to resolve the consumers' concerns in this regard.